Beber y conducir en Medellín: prevalencia y caracterización de patrones de consumo, 2014 (2015)
ABSTRACT: Every year road incidents kill 1.3 million people, cause severe injuries to 20 million and are the reason behind the loss of 40 million years of healthy life all over the world. The World Health Organization estimates that 25% of road incidents and their effects are associated with drunkenness. Methodology: to estimate the prevalence and characterize the consumption patterns of the drivers in Medellín, a random, cross-sectional and stratified measurement was taken in January 2014. During the 32 control checks 23,856 vehicles were tested; 1,611 were arrrested. A total of 845 (52,4%) were cars, while 766 (47,6%) were motorcycles. Results: of the 1,569 individuals tested for alcohol in their breath, 16 (1%) tested positive and their blood alcohol level varied from 0,24 to 3 mg of ethanol. Similarly, 7 individuals showed degree 0, 8 first degree, 0 second degree and 1 third degree. One third of the individuals had been arrested before and one in four of them had been arrested in the last month. Additionally, 36% considered they had a high probability of being arrested and 26% considered to have a moderate probability. Most drivers (60%) reported not drinking and driving, but one fifth (19%) considered that having one drink is compatible with safe driving and, even though 45% stated never drinking and driving, the other half (48%) had driven while drunk at least once in their lives. Similarly, 7% had done so several times and 25% of them did it in the last year. Finally, 26% of the individuals drove while drunk after one drink, 13% after two, three or four and remaining 30% after 5 or more drinks. Conclusion: the prevalence and patterns identified make evident the need to monitor and control the drink-and-drive behavior.